Chemical constituents of Antidesma bunius aerial parts and the anti-AGEs activity of selected compounds. (October 2022) - Nguyen-Ngoc, Hieu; Alilou, Mostafa; Derbré, Séverine; Blanchard, Patricia; Pham, Giang Nam; Nghiem, Duc Trong; Richomme, Pascal; Stuppner, Hermann; Ganzera, Markus
Abstract: Thirty-three natural products were isolated from the aerial parts of Antidesma bunius, Euphorbiaceae, a plant used in Vietnamese traditional medicine against rheumatoid arthritis. All compounds were reported the first time for this species, and nine constituents resembled undescribed natural products, noticeably three coumarinolignans with 2, 2-dimethyl-1, 3-dioxolane moiety, two cyclopeptides, and two furofuran-type lignans connected with a phenylpropanoid moiety. The individual structures were elucidated by combining NMR and MS data, and their configuration was established by NOESY and ECD experiments and NMR calculations. Compounds with sufficient amount were analyzed for their inhibition of advanced glycation endproducts (AGEs) formation, metabolites involved in many diseases like Alzheimer, joint diseases or diabetes. With IC50 values below 0.2 mM rutin and p -hydroxyphenethyl trans -ferulate showed to be moderately active, both still being 10-times more active than the positive control aminoguanidine. Graphical abstract: Image 1 Highlights: A comprehensive phytochemical characterization of Antidesma bunius is presented. Nine undescribed natural products were among the 33 isolated compounds. They represent coumarinolignans, cyclopeptides and furofuran-type lignans. Their configuration was established by ECD experiments and NMR calculations. Some compounds indicated inhibition of advanced glycation endproducts formation.